1992
DOI: 10.1128/jvi.66.10.5999-6007.1992
|View full text |Cite
|
Sign up to set email alerts
|

Fusion regulation proteins on the cell surface: isolation and characterization of monoclonal antibodies which enhance giant polykaryocyte formation in Newcastle disease virus-infected cell lines of human origin

Abstract: Newcastle disease virus (NDV)-infected HeLa and FL cells showed small polykaryocytes at about 24 h postinfection, while the addition of anti-FL-cell rabbit, rat, or mouse serum to the NDV-infected cells gave rise to giant polykaryocytes at 15 h postinfection. We isolated three monoclonal antibodies (MAbs) (4-5-1, 6-1-13, and 7-2-1) capable of enhancing giant polykaryocyte formation in NDV-infected HeLa cells. These MAbs immunoprecipitated gp80 or gp135, which were detected mainly on the surface of HeLa cells. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
24
0
1

Year Published

1994
1994
2007
2007

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(25 citation statements)
references
References 20 publications
(20 reference statements)
0
24
0
1
Order By: Relevance
“…Most recently, a set of proteins thought to enhance or induce cell fusion, initially termed FRP-1 and FRP-2 and now known to be CD98 and integrin a3, respectively (Ohta et al 1994;Ohgimoto et al 1995;Higuchi et al 1998), have been identified in a number of cell lines infected with several different viruses as well as on the surface of monocytes and macrophages. Monoclonal antibodies directed against these proteins stimulate polykaryocyte formation in CD4 1 U937 cells transfected with the HIV gp160 gene (Ohta et al 1994) and in HeLa and FL cells infected with Newcastle disease virus (Ito et al 1992). In addition, anti-FRP antibodies inhibit giant cell formation in cultures of peripheral blood monocytes (Tabata et al 1994).…”
Section: Role Of Associated Proteins In Virus±cell and Cell±cell Fusionmentioning
confidence: 99%
“…Most recently, a set of proteins thought to enhance or induce cell fusion, initially termed FRP-1 and FRP-2 and now known to be CD98 and integrin a3, respectively (Ohta et al 1994;Ohgimoto et al 1995;Higuchi et al 1998), have been identified in a number of cell lines infected with several different viruses as well as on the surface of monocytes and macrophages. Monoclonal antibodies directed against these proteins stimulate polykaryocyte formation in CD4 1 U937 cells transfected with the HIV gp160 gene (Ohta et al 1994) and in HeLa and FL cells infected with Newcastle disease virus (Ito et al 1992). In addition, anti-FRP antibodies inhibit giant cell formation in cultures of peripheral blood monocytes (Tabata et al 1994).…”
Section: Role Of Associated Proteins In Virus±cell and Cell±cell Fusionmentioning
confidence: 99%
“…(4,5) These mAbs immunoprecipitated gp80 and gp135, which were detected on the surface of cells of human origin. (4) These molecules were designated fusion regulatory protein (FRP)-1 and -2 and were identified as heavy chains of CD98/4F2 and integrin ␣3, respectively. (5)(6)(7)(8)(9)(10) In this study, we developed a human blood monocyte culture system using anti-FRP-1 antibody, in which osteoclast-like polykaryocytes are formed without any other trigger of osteoclast formation.…”
Section: Introductionmentioning
confidence: 99%
“…The cell membranes of K562 cells are considered to be resistant to virus-induced cell fusion (fusion from without or fusion from within). Membrane fusion is regulated by many host factors including membrane fluidity, cytoskeletal systems, and FRPs system (5,7,13). Disruption of microfilaments resulted in inhibition of cell fusion, while inhibitor to microtubules enhanced virus-induced cell fusion (13).…”
Section: Discussionmentioning
confidence: 99%
“…Antibodies. Polyclonal antibodies and monoclonal antibodies (mAbs) directed against hPIV-2 or NDV were described previously (5,11) Isotopic labeling of virus-infected cells, Radioimmuno-precipitation assay (RIPA) and sodium dodecyl sulfate-polyacrylamide gel electrophoresis (SDS-PAGE). Approximately 2ϫ10 6 cells were infected with virus at an input multiplicity of infection (m.o.i.)…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation